AB0460 Causes of Early and Late Death of Patients with Systemic Lupus Erythematosus over A 10-Year Period. (15th July 2016) - Padjen, I.; Erceg, M.; Cerovec, M.; Mayer, M.; Stevanović, R.; Anić, B.
Abstract : Background: Causes of death (CODs) of patients with systemic lupus erythematosus (SLE) comprise active SLE and comorbidities that develop as a result of SLE and immunosuppressive therapy: infections, cardiovascular disease and malignant tumors. Active disease and infections are typical causes of early death, while cardiovascular disease typically causes late death. However, COD frequencies depend on the source population and data ascertainment method. Objectives: To identify and compare causes of early and late death of SLE patients deceased during a ten-year period. Methods: We retrospectively identified SLE patients followed-up by our Department, deceased between 2002 and 2011, and included patients with ≥4 classification criteria of the American College of Rheumatology (ACR), ≥18 years of age and Croatian residency at the time of death. Death and causes of death were retrospectively identified using patient medical records, as well as death certificates and autopsy reports, when available. We also matched data on all SLE patients that visited our Department from 2002 to 2011 with the National Mortality Database. We classified CODs into five categories: active SLE, cardiovascular disease, infection, malignant tumor and other. More than one COD category was possible in a single patient. We compared the frequencies of each COD category between patients deceased within and after 5 years following diagnosis (early vs. late death). Frequencies were compared using the χ 2 and Fisher's exact test, and continuous variables using the t-test and Mann-Whitney U test. The study was approved by the local ethics committee. Results: We identified 90 deceased patients (68 females, 22 males; 21 in the early death group (EDG), 69 in the late death group (LDG)). EDG patients were older than LDG patients at diagnosis (mean age±SD: 56±15 vs. 46±17 years; p=0.005), but there was no difference between the age at death (mean age±SD: 58±15 years for all patients). Patients were followed-up for a median of 10 years (IQR: 5–15 years). LDG patients fulfilled a higher number of ACR criteria compared to EDG patients (median, IQR: 6, 5–7 vs. 5, 4–6; p=0.018). No difference between COD category frequencies was detected between EDG and LDG. Nevertheless, infections and active SLE were leading causes of early death (9/21 and 8/21, respectively), while cardiovascular disease was the most frequent cause of late death (30/69), followed by infection and active SLE (21/69 and 18/69, respectively)(Table). SLE was mentioned in the death-related medical records of only 41/90 patients. Conclusions: Infections and active SLE are leading causes of early death, while cardiovascular disease is the most frequent cause of late death in SLE. Lack of recording of SLE in death-related medical records requires matching of clinical data with a complementary source, such as a population-based mortality database, to identify deceased SLE patients. References: Nossent J et al. Lupus 2007;16:309–17. Disclosure of Interest: None declared